Assessing and Comparing Global Health Competencies in Rehabilitation Students. (7th December 2013) - Veras, Mirella; Pottie, Kevin; Cameron, Debra; Dahal, Govinda P.; Welch, Vivian; Ramsay, Tim; Tugwell, Peter
Abstract : Purpose . Globalization is contributing to changes in health outcomes and healthcare use in many ways, including health professionals' practices. The objective of this study was to assess and compare global health competencies in rehabilitation students. Method . Online cross-sectional survey of physiotherapy and occupational therapy students from five universities within Ontario. We used descriptive statistics to analyze students' perceived knowledge, skills, and learning needs in global health. We used Chi-square tests, with significance set atP < 0.05, to compare results across professions. Results . One hundred and sixty-six students completed the survey. In general, both physiotherapy and occupational therapy students scored higher on the "relationship between work and health, " "relationship between income and health, " and "socioeconomic position (SEP) and impact on health" and lower on "Access to healthcare for low income nations, " "mechanisms for why racial and ethnic disparities exist, " and "racial stereotyping and medical decision making." Occupational therapy students placed greater importance on learning concerning social determinants of health (P = 0.03 ). Conclusion . This paper highlights several opportunities for improvement in global health education for rehabilitation students. Educators and professionals should consider developing strategies to address these needs and provide more global health opportunities in rehabilitation training programs.